APPLICATION OF INNOVATIVE TECHNOLOGIES AT FOOD ENTERPRISES - N. D. Dmitriev; E. A. Rogozina (Вестник университета, 2020)
For today, innovative technologies are the engine of progress and without use of them it is impossible to talk about sustainable development. Some industries can afford the slow introduction of innovations; for other areas of activity, the introduction of innovations is a prerequisite for optimal functioning in market conditions. The latter also includes the food industry, whose market position is directly dependent on innovative activity. The issue of the possible use of innovative technologies in the food industry has been studied in the article. To identify the main problems, it has been proposed to emphasize the factors on which the innovative development of the food industry and the duration of the technology development cycle depend. An example of the use of innovations in food production, including patent activity on end-to-end technologies has been given. Based on the research, recommendations for conducting innovative activities in the food production industry have been given.